Inter-organellar Communication in Parkinson's and Alzheimer's Disease: Looking Beyond Endoplasmic Reticulum-Mitochondria Contact Sites - Vrijsen, Stephanie; Vrancx, Céline; Del Vecchio, Mara; Swinnen, Johannes V.; Agostinis, Patrizia; Winderickx, Joris; Vangheluwe, Peter; Annaert, Wim (Frontiers in Neuroscience, 2022)
Neurodegenerative diseases (NDs) are generally considered proteinopathies and although this may initiate/drive disease in familial cases, onset in sporadic diseases may originate from a gradual build-up of organellar dyshomeostasis. Herein, endolysosomal abnormalities, mitochondrial dysfunction (and associated ROS), endoplasmic reticulum (ER) stress, and altered lipid metabolism are commonly observed in early preclinical stages of major NDs, including Parkinson’s disease (PD) and Alzheimer’s disease (AD). Among the multitude of underlying defective molecular mechanisms that have been suggested in the past decades, dysregulation of inter-organellar communication through the so-called membrane contact sites is becoming increasingly apparent. Although membrane contact sites (MCSs) exist between almost every other type of subcellular organelle, to date, most focus has been put on defective communication between the endoplasmic reticulum and mitochondria in NDs, given these compartments are critical in neuronal survival. Contributions of other contact sites, notably those with endo/lysosomes and lipid droplets are emerging, supported as well by genetic studies, identifying genes functionally involved in lysosomal homeostasis. In this review, we summarize the molecular identity of the organelle interactome in yeast and mammalian cells, and critically evaluate the evidence supporting the contribution of disturbed membrane contact sites to the general inter-organellar dyshomeostasis in neurodegenerative diseases, taking PD and AD as major examples.